Monoclonal antibody therapy demonstrates increased virulence of a lineage VII strain of Lassa virus in nonhuman primates - Courtney Woolsey; Robert W. Cross; Abhishek N. Prasad; Krystle N. Agans; Viktoriya Borisevich; Daniel J. Deer; Natalie S. Dobias; Alyssa C. Fears; Mack B. Harrison; Megan L. Heinrich; Karla A. Fenton; Robert F. Garry; et al. (Emerging Microbes and Infections)
Lassa virus (LASV) is a World Health Organization (WHO) priority pathogen that causes high morbidity and mortality. Recently, we showed that a combination of three broadly neutralizing human monoclonal antibodies known as Arevirumab-3 (8.9F, 12.1F, 37.2D) based on the lineage IV Josiah strain protected 100% of cynomolgus macaques against heterologous challenge with lineage II and III strains of LASV when therapy was initiated beginning at day 8 after challenge. LASV strains from Benin and Togo represent a new lineage VII that are more genetically diverse from lineage IV than strains from lineages II and III. Here, we tested the ability of Arevirumab-3 to protect macaques against a LASV lineage VII Togo isolate when treatment was administered beginning 8 days after exposure. Unexpectedly, only 40% of treated animals survived challenge. In a subsequent study we showed that Arevirumab-3 protected 100% of macaques from lethal challenge when treatment was initiated 7 days after LASV Togo exposure. Based on our transcriptomics data, successful Arevirumab-3 treatment correlated with diminished neutrophil signatures and the predicted development of T cell responses. As the in vitro antiviral activity of Arevirumab-3 against LASV Togo was equivalent to lineage II and III strains, the reduced protection in macaques against Togo likely reflects the faster disease course of LASV Togo in macaques than other strains. This data causes concern regarding the ability of heterologous vaccines and treatments to provide cross protection against lineage VII LASV isolates.